2015
DOI: 10.1177/1932202x15621905
|View full text |Cite
|
Sign up to set email alerts
|

Choosing Among Multiple Achievement Measures

Abstract: Practitioners and researchers interested in understanding student achievement, its predictors, and how it relates to other student outcomes are likely unaware of how the source information about achievement may offer subtly different pictures. This study applies multitrait–multimethod (MTMM) confirmatory factor analysis (CFA) within a structural equation modeling (SEM) framework to student achievement data to demonstrate empirically how commonly used measures of student achievement may reflect different inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…It has been used with many studies on personality and academic achievement, as a criterion variable (Wagerman and Funder, 2007;Milienos, 2013, 2015). However, limitations of the GPA, as a study variable, have been reported as the accuracy of students' self reported grades may vary with actual student performance (Kuncel et al, 2005;Dickinson and Adelson, 2016). Research results suggests that self reported grades are reasonably good reflections of actual grades with high ability and good grade point average (Kuncel et al, 2005), while this is not the case for low GPA students.…”
Section: Achievementmentioning
confidence: 96%
“…It has been used with many studies on personality and academic achievement, as a criterion variable (Wagerman and Funder, 2007;Milienos, 2013, 2015). However, limitations of the GPA, as a study variable, have been reported as the accuracy of students' self reported grades may vary with actual student performance (Kuncel et al, 2005;Dickinson and Adelson, 2016). Research results suggests that self reported grades are reasonably good reflections of actual grades with high ability and good grade point average (Kuncel et al, 2005), while this is not the case for low GPA students.…”
Section: Achievementmentioning
confidence: 96%
“…The utilization of both a localized derived student achievement measure (i.e., GPA) coupled with analysis of a nationally normed standardized test (i.e., ACT) was more holistic and appropriate as differing measures of student achievement can explain different student characteristics (Kelepolo, 2011). GPA is a more subjective multidimensional achievement measure that includes a variety of student and teacher variables such as personality and motivation (Dickinson & Adelson, 2015;Jaramillo & Spector, 2004). The ACT aims to take a more objective approach by providing insight on college readiness and content knowledge (Marchetti et al, 2015).…”
Section: Measuring Academic Achievementmentioning
confidence: 99%
“…In the current practice of academic management in classes of college, the main methods of comprehensive evaluation of students' performance are the cumulative method of raw scores, the method of arithmetic averages, the method of average academic performance, and the method of principal component analysis. Some scholars have also developed a factor analysis model based on the GPA model with the modifcation of factor analysis superimposed on it [7]. Te model is based on the factor analysis.…”
Section: Introductionmentioning
confidence: 99%